A importância das consultoras no apoio às micro, pequenas e médias empresas - novas limitações e desafios impostos às empresas portuguesas - Brito, Andreia Filipa Ramos de (2021)
The importance of micro, small and medium-sized enterprises for the European and national economies is undeniable. These represent almost the entire Portuguese business reality. However, due to their small size, they face numerous challenges daily. The start of the internationalization process and the expansion to international markets are two examples of the various challenges imposed on Portuguese micro and SMEs. Digitization and corporate sustainability are also significant challenges for which Portugueses SMEs increasingly, must be prepared. Given their importance, these are a priority in the European Union and, consequently, in the national policies of all Member States. Hence, several measures were developed to encourage and promote its action, not only at the measures were developed to encourage and promote its action, not only at the European but also at the international level. The present report aims to carry out a critical evaluation of the curricular internship that took place at BWS Consulting, for the conclusion of the Master Degree in Entrepreneurship and Internacionalization. This report also intended to deliberate on the importance of consulting companeis in supporting micro, small and medium-sized companies, how it helps them identify difficulties, and how solutions are found to overcome these adversities. In Portugal, despite its late development, the consultancy sector has registered significant growth rates over the years, proving that these institutions are a beneficial element in terms of supporting and improving operations and in the strategic development of SMEs